2008
DOI: 10.1111/j.1467-2979.2008.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shifts in marine fisheries genetics: ugly hypotheses slain by beautiful facts

Abstract: Introduction 334Population structure in marine fishes 335 Paradigm shift 335Genetic differentiation in space and time 336Population connectivity in marine fishes on a fine scale 338Spatial and temporal scale of adaptation 339 Paradigm shifts 339Spatial scale of adaptive differentiation 340Temporal scale of adaptive differentiation 342 AbstractBy providing new approaches to the investigation of demographic and evolutionary dynamics of wild populations, molecular genetics has led to fundamental changes in our un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
550
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 538 publications
(584 citation statements)
references
References 286 publications
(371 reference statements)
29
550
3
2
Order By: Relevance
“…However, the confirmation of the slope by a completely different marker system further supports the genetic pattern itself and the underlying basis of limited dispersal distances, despite a lengthy larval period and highly migratory adults. It also supports the increasingly acknowledged pattern of subtle population structure in species with no obvious barriers to dispersal, such as marine fishes (Hauser & Carvalho, 2008). …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, the confirmation of the slope by a completely different marker system further supports the genetic pattern itself and the underlying basis of limited dispersal distances, despite a lengthy larval period and highly migratory adults. It also supports the increasingly acknowledged pattern of subtle population structure in species with no obvious barriers to dispersal, such as marine fishes (Hauser & Carvalho, 2008). …”
Section: Discussionsupporting
confidence: 70%
“…Moreover, populations at the southern edge of the species’ distribution may be old and harbor genetic variation important for the survival and evolution of a species (i.e., rear edge effect; Hampe & Petit, 2005). These stabilizing characteristics may become increasingly important as climate change progresses (Hauser & Carvalho, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Adaptive divergence can occur over much shorter time scales than can neutral genetic differentiation (Endler 1986, Cano et al 2008, resulting in genetic differentiation of a greater magnitude for selected versus neutral loci (Beaumont & Balding 2004) : 177-195, 2010 therefore inappropriate for making inferences about population processes, such as migration rates and effective population size, they can serve an important function in genetic stock identification (Nielsen et al 2006, ICES 2009). The adaptive differences underlying variation at selected loci may have important management implications (Crandall et al 2000, Conover et al 2006, Hauser & Carvalho 2008, ICES 2009.…”
Section: Natural Selection and Local Adaptationmentioning
confidence: 99%
“…This classical view of marine fish species (Hauser & Carvalho 2008) was supported by tagging studies that demonstrated long distance migrations (Templeman 1974) and by early genetic studies that revealed high levels of gene flow (Ward et al 1994). This perspective influenced management regimes, such that many marine fisheries are managed as broadly distributed, panmictic populations .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation